2016
DOI: 10.1021/acssensors.5b00289
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Operated Signal Transduction by Ion Nanogating (STING) Amplifier for Nanopore Sensors: Design and Analytical Application

Abstract: In this report, we demonstrated a handheld wireless voltage-clamp amplifier for current measurement of nanopore sensors. This amplifier interfaces a sensing probe and connects wirelessly with a computer or smartphone for the required stimulus input, data processing and storage. To test the proposed Signal Transduction by Ion Nanogating (STING) wireless amplifier, in the current study the system was tested with a nano-pH sensor to measure pH of standard buffer solutions and the performance was compared against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Solving the time and selectivity challenges would open the path to a new generation of nanopore-based biomolecular quantitative analysis systems 6,8,9 . These would provide single molecule resolution, could be calibration-free as they rely on counting alone 10 , are compatible with bulk manufacture 11 , and require simple electronics that are easily miniaturised for point-of-care and mobile use 1217 .…”
Section: Introductionmentioning
confidence: 99%
“…Solving the time and selectivity challenges would open the path to a new generation of nanopore-based biomolecular quantitative analysis systems 6,8,9 . These would provide single molecule resolution, could be calibration-free as they rely on counting alone 10 , are compatible with bulk manufacture 11 , and require simple electronics that are easily miniaturised for point-of-care and mobile use 1217 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the nanopore has emerged as an attractive, powerful, and sensitive single-molecule platform that has been used for a wide range of applications including rapid gene sequencing and the detection of various analytes such as metal ions, , PEG polymer, , DNA and microRNA, DNA–protein interactions, peptides, , protein and trypsin in the mixture. Recently, it was also shown that the sensing capabilities of solid-state nanopore can be enhanced in combination with DNA origami . A hand-held wireless voltage-clamp amplifier that interfaces a sensing probe of nanopore was constructed to enable a miniaturized wireless platform that can be conveniently operated with a smartphone . In particular, an aerolysin nanopore was demonstrated to first exhibit impressive advantage in the discrimination of multianalytes in the mixtures, which was attributed to its narrow diameter and the strong electrostatic interactions between the aerolysin and the oligonucleotides .…”
mentioning
confidence: 99%
“…31 A hand-held wireless voltage-clamp amplifier that interfaces a sensing probe of nanopore was constructed to enable a miniaturized wireless platform that can be conveniently operated with a smartphone. 32 In particular, an aerolysin nanopore was demonstrated to first exhibit impressive advantage in the discrimination of multianalytes in the mixtures, which was attributed to its narrow diameter and the strong electrostatic interactions between the aerolysin and the oligonucleotides. 33 All these advancements indicate that the nanopore technique holds a great potential for wide practical applications.…”
mentioning
confidence: 99%
“…The robustness of the portable nanopore sensing system was confirmed under different temperature, humidity, and surrounding electromagnetic noise conditions. Ozel et al 223 developed a low-noise voltage-clamp amplifier that has a small size and can be powered by a 9 V battery and connected wirelessly to a computer or a smartphone for nanopore measurement (Fig. 18b).…”
Section: Outlook Of Emerging Trends In Nanopore Sensing For Quantitat...mentioning
confidence: 99%